Peran Sistem Informasi Akuntansi Dalam Meningkatkan Kinerja Karyawan Pada PT. Multi Karya Komponen Bogor - Syamsul Hadi (Peneliti.net, 2022)
The purpose of knowing the role of accounting information systems has an effect on improving employee performance at PT. Multi Component Works. The method used is qualitative, by means of observation and interviews. The population in this study were HRD, Marketing Staff, and employees of PT. Multi Component Works. Based on the results of the study, it can be concluded that the existence of an accounting information system has a very important influence on employee performance, because with an employee job information system it will be easier, coordinated, accurate, and accountable, because each final report must be in accordance with the final results. and in accordance with company targets. This shows that the better an accounting information system is implemented in a company, the better the performance of employees in the company will be. the company should provide special training in operating computers to employees if there is new technologyI